Efektivitas Penilaian Tingkat Kesehatan Perbankan Menggunakan Metode RGEC pada Bank Rakyat Indonesia Tahun 2018-2020 - Desy Pratiwi (Manajemen Kreatif Jurnal, 2024)
This research aims to determine the effectiveness of assessing banking soundness levels using the PT RGEC method. Bank Rakyat Indonesia Tbk in 2018-2020. In this research, researchers used several research variables which include Risk Profile (NPL and LDR), Good Corporate Governance (GCG), Earnings (ROA, ROE, NIM, BOPO) and Capital (CAR). Based on research on the effectiveness of assessing the level of banking health at PT. Bank Rakyat Indonesia Tbk, using the RGEC method, shows that the bank’s health status is in accordance with the standards set by Bank Indonesia regulations. For the 2018 period it can be concluded that PT. Bank Rakyat Indonesia Tbk received a composite rating of 1, namely "Very Healthy" with a composite score of 90%, for the 2019 period it can be concluded that PT. Bank Rakyat Indonesia Tbk received a composite rating of 1, namely "Very Healthy" with a composite score of 92.5%, for the 2020 period it can be concluded that PT. Bank Rakyat Indonesia Tbk received a composite rating of 1, namely "Very Healthy" with a composite score of 90%. As well as the bank’s health level in terms of Risk Profile, Good Corporate Governance, earnings and Capital indicators at PT. Bank Rakyat Indonesia Tbk for 2018-2020 is "Very Healthy". It is hoped that future researchers will be more careful in carrying out calculations, can use better methods than this research and can add ratios so that the results of the research are more robust.